Recent results on the degradation of white LEDs for lighting - Meneghesso, G; Meneghini, M; Zanoni, E (Journal of physics. D, Applied physics, 2010)
Over the last years, GaN-based light-emitting diodes (LEDs) have been shown to be excellent candidates for the realization of high-efficiency light sources. White LEDs based on phosphor conversion can reach record efficiencies in excess of 150 lm W −1 , as demonstrated by several manufacturers and research groups. However, the reliability of white LEDs is still limited by a number of issues that must be addressed before these devices can find wide application in the market. This paper gives an overview on the most important physical mechanisms that limit the reliability of GaN-based LEDs for application in solid-state lighting. Starting from general considerations on the reliability of state-of-the-art white LEDs, the following degradation mechanisms are described in detail: (i) the degradation of the active layer of LEDs due to increased non-radiative recombination and reverse-bias stress; (ii) the degradation of the package/phosphor system, with subsequent worsening in the chromatic properties of the LEDs; (iii) the failure of GaN-based LEDs submitted to electrostatic discharge events. The data presented in this paper are critically compared with those reported in the literature.